E-005 Short-term Outcomes of Acute Ischemic Stroke Patients with MCA/ICA Occlusion Excluded for Intra-arterial Reperfusion Therapy. (26th July 2014) - Honarmand, A; Beck, R; Soltanolkotabi, M; Ansari, S; Shaibani, A; Daruwalla, V; Hurley, M
Abstract : Introduction: Large-vessel occlusions account for 45% of patients with acute ischemic stroke (AIS) presenting to the emergency departments in the United States. Many of these patients may not be eligible candidates for intravenous tPA therapy; however, they may benefit from receiving intra-arterial therapy (IAT). Optimal patient selection plays a pivotal role in identification of those AIS patients who may benefit from IAT. However, no method has been introduced as the gold standard for patient selection among neurointerventionalists in the clinical practice. Therefore, many of the stroke patients with large vessel occlusion presenting in the acute setting do not receive IAT. We aimed to review the short-term outcome of AIS patients with large vessel occlusion who were not selected for IAT. Methods: We retrospectively reviewed consecutive AIS patients with National Institute of Health Stroke Scale (NIHSS) score of more than 8 and CTA/MRA verified MCA/ICA occlusion who did not receive endovascular thrombectomy/thrombolysis treatment. Data were collected on demographics, initial NIHSS score, the cause for not being eligible for endovascular intervention, and mortality rate during the first 30 days. Eligibility for undergoing IA thrombectomy/thrombolysis treatment based on CT/MR perfusion imaging profiles was defined as CBV/DWI infarct core 20% infarct core. Results: Thirty one AIS patients (19 F/12 M; mean age of 78.1(32–93; SD: ±13.44 years) were studied. Mean and median baseline NIHSS score were 20.06 (8–40; SD: ± 8.25) and 19, respectively. Mortality in the first 30 days was 38.7% (12/31) and 6 patients (20%) were referred to hospice. Among fourteen patients who did not undergo endovascular thrombectomy/thrombolysis reperfusion therapy due to the unfavorable perfusion profile, six patients expired and 4 patients were referred to the hospice, in the first 30 days. Seventeen patients were not intervened due to improvement in NIHSS score following receiving intravenous tPA, advanced age, severely high NIHSS score, and high risk clinical profile for intervention. Among these patients, six patients expired and two patients were referred to hospice. Conclusion: In this cohort of patients, we observed relatively high mortality rate and poor short-term clinical outcomes in AIS patients with large vessel occlusion who were not selected for IAT. Patients excluded from receiving IAT using imaging-based methods, generally had worse outcomes compared with those patients who were selected based on clinical evaluation. Efforts should be made to develop a standard and accurate patient selection method for identification of the optimum number of AIS patients with large vessel occlusion who may benefit from IAT. Disclosures: A. Honarmand: None. R. Beck: None. M. Soltanolkotabi: None. S. Ansari: None. A. Shaibani: None. V. Daruwalla: None. M. Hurley: None.